Platelet Mass Predicts Intracranial Hemorrhage in Neonates With Gram-negative Sepsis. Issue 7 (October 2015) - Mitsiakos, Georgios; Pana, Zoe-Dorothea; Chatziioannidis, Ilias; Piltsouli, Dimitra; Lazaridou, Eleni; Koulourida, Vasiliki; Papadimitriou, Aikaterini; Nikolaidis, Nikolaos; Roilides, Emmanuel
Abstract : Neonatal sepsis due to gram-negative bacteria is associated with severe hemorrhagic conditions, such as intracranial hemorrhage (ICH). The aim of the study was to investigate the significance of platelet (PLT) count and platelet mass (PM) in predicting promptly neonatal ICH. Demographics, species, PLT, PM, ICH, and outcome for neonates with gram-negative sepsis for the period 2005 to 2012 were retrospectively recorded. Eighty-four infants were enrolled with median gestational age 30 weeks, median birthweight 1481.5 g, and median age at sepsis diagnosis 23 days. The most frequently isolated bacteria were Enterobacter spp. (38.1%). ICH occurred in 16 neonates (19%), whereas the mortality rate was 25% (21 neonates). The median PLT count and PM at days 1, 2, and 3 after diagnosis of gram-negative sepsis was significantly associated with the presence of ICH. Regression analysis revealed the cutoff predictive value of 355 fL/nL for the PM at day 3 (area under the curve: 75, sensitivity 90%, P =0.002). PM levels could play an important role in predicting the occurrence of ICH in high-risk neonates.